Assessment of the Effect of Erenumab on Efficacy and Quality-of-Life Parameters in a Cohort of Migraine Patients With Treatment Failure in Cyprus - Tziakouri, Andria; Tsangari, Haritini; Michaelides, Costas (Frontiers in Neurology, 2021)
Erenumab is the first human monoclonal antibody, to be approved as a selective therapy for migraine prophylaxis in adults. This study assessed, in a real-world setting, the efficacy of erenumab and its impact on the quality of life (QoL) of Cypriot migraine patients who had failed several treatments in the past. Erenumab was prescribed as a stand-alone or as an add-on therapy to sixteen patients with chronic migraine. The first component of the study examined migraine parameters before and after erenumab therapy and included an interim 3-month subjective assessment. In the second component, the patients were asked to complete the validated Migraine-Specific Quality-of-Life Questionnaire Version 2.1 (MSQV2.1), during the last month of their individual treatment as a measure of the QoL. The results showed a statistically significant improvement in almost all migraine parameters following erenumab treatment. In the three-month interval assessment, 81.3% of the patients reported an improvement in their mental well-being, anxiety, and depression levels, with more than 80% of the patients reporting improvement in almost all assessed migraine parameters. MSQV2.1 indicated a good health status in all three domains (mean values >60 on a scale 0-100) with the “Role function preventative” domain having the highest health scores (85). Over a period of six months, erenumab was safe, well-tolerated, and effective in preventing migraine symptoms and improving HR-QoL. We conclude that this novel medication which is not yet part of the national formulary in Cyprus, may be a cost-effective solution in reducing the disease burden of chronic migraine.